Intrapleural streptokinase for the treatment of chylothorax - Kuan, Yeh Chunn; How, Soon Hin; Ng, Teck Han; Abdul Rani, Mohammed Fauzi (Daedalus Enterprises, Inc., 2011)
Chylothorax is suspected when milky white turbid fluid is obtained from thoracocentesis. Conservative management usually involves intercostal tube drainage, dietary restriction, and total parenteral nutrition. Surgery is indicated when conservative management fails. We describe a young woman with idiopathic chylothorax who failed conservative therapy but refused surgery. We instilled intrapleural streptokinase, which improved her condition.